#### Answer

$\lim\limits_{x \to 0}(x^{2}-1)(2-cosx) = -1$

#### Work Step by Step

$\lim\limits_{x \to 0}(x^{2}-1)(2-cosx) = \lim\limits_{x \to 0}(2x^{2}-x^{2}cosx - 2 + cosx) = 0+0-2+1 = -1$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$\lim\limits_{x \to 0}(x^{2}-1)(2-cosx) = -1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.